Dilute doping, defects, and ferromagnetism in metal oxide systems - Ogale, Satishchandra B. (Advanced Materials, 2010)
Over the past decade intensive research efforts have been carried out by researchers around the globe on exploring the effects of dilute doping of magnetic impurities on the physical properties of functional non-magnetic metal oxides such as TiO2 and ZnO. This effort is aimed at inducing spin functionality (magnetism, spin polarization) and thereby novel magneto-transport and magneto-optic effects in such oxides. After an early excitement and in spite of some very promising results reported in the literature, this field of diluted magnetic semiconducting oxides (DMSO) has continued to be dogged by concerns regarding uniformity of dopant incorporation, the possibilities of secondary ferromagnetic phases, and contamination issues. The rather sensitive dependence of magnetism of the DMSO systems on growth methods and conditions has led to interesting questions regarding the specific role played by defects in the attendant phenomena. Indeed, it has also led to the rapid re-emergence of the field of defect ferromagnetism. Many theoretical studies have contributed to the analysis of diverse experimental observations in this field and in some cases to the predictions of new systems and scenarios. In this review an attempt is made to capture the scope and spirit of this effort highlighting the successes, concerns, and questions.

Dye sensitized solar cell (DSSC) by a novel fully room temperature process: a solar paint for smart windows and flexible substrates - Agarkar, Shruti A.; Dhas, Vivek V.; Muduli, Subas; Ogale, Satishchandra B. (RSC Advances, 2012)
We report the development of a titania-nanoparticle-based solar paint which gives a conversion efficiency of 3.6% on FTO/glass substrates under fully room temperature processing. The paint cures quickly saving time in the cell fabrication process. Even on a flexible ITO/PET substrate efficiency of 2.4% was achieved. We present and analyze the results of described materials and device property characterizations.

Defects in chemically synthesized and thermally processed ZnO nanorods: implications for active layer properties in dye-sensitized solar cells - Das, Partha Pratim; Agarkar, Shruti A.; Mukhopadhyay, Soumita; Manju, Unnikrishnan; Ogale, Satishchandra B.; Devi, P. Sujatha (Inorganic Chemistry, 2014)
We have carried out the effect of post annealing temperatures on the performance of solution-grown ZnO rods as photoanodes in dye-sensitized solar cells. Keeping our basic objective of exploring the effect of native defects on the performance of DSSC, we have synthesized ZnO rods having length in the range of 2-5 mu m by a modified sonication-induced precipitation technique. We performed extensive characterization on the samples annealed at various temperatures and confirmed that annealing at 300 degrees C results in ZnO rods with minimum native defects that have been identified as doubly ionized oxygen vacancies. The electron paramagnetic resonance measurements on the samples, on the other hand, confirmed the presence of shallow donors in the low temperature annealed samples. We also carried out electrochemical impedance measurements to understand the transport properties at different interfaces in the solar cell assembly. We could conclude that solution-processed ZnO rods annealed at 300 degrees C are better suited for fabricating DSSC with improved efficiency (1.57%), current density (5.11 mA/cm(2)), and fill factor (45.29%). On the basis of our results, we were able to establish a close connection between the defects in the metal oxide electron transporting nano system and the DSSC performance.